Optimization of Mosque Resources and Management in Community Empowerment: Influence and Mediation of Functions - Faizal, Faizal (CV. Tripe Konsultan, 2024)
This study aims to analyze the influence of mosque resources and management on community empowerment with the function of mosques as a mediating variable. Mosques have the potential to become a center for community empowerment through optimal management and management of resources. This study uses a quantitative approach with regression analysis to measure the direct and indirect effects of mosque resources and management on community empowerment. The results of the study show that mosque resources have a significant influence on the welfare of the community. The management of the mosque also greatly affects the function of the mosque, which acts as a mediator between mosque resources and community empowerment. In conclusion, optimizing resources and improving mosque management can support improving the welfare of the surrounding community. This study recommends that mosque managers develop mosque-based empowerment programs that are sustainable and inclusive.